Nota sobre a possibilidade de aproveitamento de casca de cacau na fabricação de geléia - Marcondes Borges , José (Revista Ceres, 2025)
Preliminary studies have shown that jelly can be made from cacao pod husks, which is similar in taste and colour to the more usual jelly made from the cacao bean mucilage common- ly known as the "sweatings". No differences were noted for either odour or consistency, although it was found to be slightly more difficult to make jelly from the husks than from the "sweatings". There were some differences between the husk jelly made from endocarp (the scrapings from the inside of the fruit) and the exocarp (the pod shell).